2012
DOI: 10.1186/1479-5876-10-171
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ROCK1 dependent contractility in fibroblast from chronic obstructive pulmonary disease patients

Abstract: BackgroundDuring wound healing processes fibroblasts account for wound closure by adopting a contractile phenotype. One disease manifestation of COPD is emphysema which is characterized by destruction of alveolar walls and our hypothesis is that fibroblasts in the COPD lungs differentiate into a more contractile phenotype as a response to the deteriorating environment.MethodsBronchial (central) and parenchymal (distal) fibroblasts were isolated from lung explants from COPD patients (n = 9) (GOLD stage IV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…The present data implicate an important issue that severe COPD patients may have a reduced repair mechanism in the ECM structure of the collagen network in the distal lung. Previous studies support our findings that changes in ECM synthesis are involved in pathologic conditions of COPD [17] and that fibroblasts from COPD patients may have a reduced or defective capacity of tissue repair [17,18,28]. Conversely, in this study, fibroblasts from COPD patients showed not only an altered production of prostacyclin and proteoglycans, but also a general decrease in proliferative rate and migratory capacity and an increased contractile phenotype compared to fibroblasts from control subjects.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present data implicate an important issue that severe COPD patients may have a reduced repair mechanism in the ECM structure of the collagen network in the distal lung. Previous studies support our findings that changes in ECM synthesis are involved in pathologic conditions of COPD [17] and that fibroblasts from COPD patients may have a reduced or defective capacity of tissue repair [17,18,28]. Conversely, in this study, fibroblasts from COPD patients showed not only an altered production of prostacyclin and proteoglycans, but also a general decrease in proliferative rate and migratory capacity and an increased contractile phenotype compared to fibroblasts from control subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, we could not detect any MMP-9 synthesis in the present study. Importantly, distally-derived fibroblasts from severe COPD patients demonstrated a more contractile phenotype in this study, probably due to enhanced ROCK1 activity [18], than fibroblasts from control subjects, and treatment with iloprost attenuated the contractile capacity to the same level as fibroblasts from control subjects in the present study. The inhibitory effect of prostacyclin analogs on fibroblast gel contractions has previously been shown in healthy lung fibroblasts and the response was mediated through cAMP activation of PKA [48].…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations